Identità dell’artista e rapporto uomo donna - Panzera, Anna Maria (Il sogno della farfalla, 2006)
In the history of Western art there have not been many clear representations of the male-female relationship. But the most important question to consider is whether history of art studies have ever looked into this theme. If we consider female representations from prehistory to Aegean Art, from Minoic Art to Etruscan Art, from Classical Art to Contemporary Art, are we in a position to assume that each shape hints at a particular form of relationship between men and women? If so, what can we say about Pablo Picasso’s monstrous images? Can they be taken literally? Perhaps, those images reveal an “innate” heterosexuality, that we find in complete contrast with the only “cultural” representation of male-female relationships deemed possible by the West.